2008
DOI: 10.4103/0972-0707.45252
|View full text |Cite
|
Sign up to set email alerts
|

The influence of salivary contamination on the shear bond strength of two newer generation dentin bonding agents - Anin vitrostudy

Abstract: Background and Objectives:To investigate whether salivary contamination during various stages of the bonding procedures of Xeno III and Clearfil SE Bond influences shear bond strength.Materials and Methods:The occlusal surfaces of thirty six maxillary premolar teeth were ground and divided into two groups containing eighteen specimens each, which was subdivided into three sub groups: Group I - Xeno III, Group II - Clearfil SE Bond, Subgroup A - Uncontaminated (control), Subgroup B - Contaminated with saliva be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 6 publications
(6 reference statements)
1
12
0
Order By: Relevance
“…This could be due to the adsorption of glycoproteins onto the poorly polymerized adhesive surface, which results in oxygen inhibition. [1518] The result of the present study is in agreement with the result of an earlier study done by Fritz et al . using a one-step adhesive, which concluded that in a one bottle adhesive system, any contamination of the already cured adhesive layer seriously compromises the bond strength.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could be due to the adsorption of glycoproteins onto the poorly polymerized adhesive surface, which results in oxygen inhibition. [1518] The result of the present study is in agreement with the result of an earlier study done by Fritz et al . using a one-step adhesive, which concluded that in a one bottle adhesive system, any contamination of the already cured adhesive layer seriously compromises the bond strength.…”
Section: Discussionsupporting
confidence: 93%
“…[815]Adhesive application after rinsing and drying of contaminants showed better bond strength. This is because cleaning procedure was able to remove the contaminants from tooth surface andalso render a better adhesion, which is in agreement with the results obtained by many studies.…”
Section: Discussionmentioning
confidence: 99%
“…The literature about the effect of saliva contamination on the bond strength facilitated by self-etch adhesives is ambiguous. Some studies conveyed that the self-etching adhesives are more vulnerable to salivary contamination in the dentine [5,[12][13][14][15][16][17]; in contrast, few studies ascertained that there was no significant difference due to salivary contamination in bond quality while bonding to the dentine [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] So, the separately light-cured P90 primer can actually be regarded as a one-step self-etch adhesive. [ 12 ] Several saliva contamination studies[ 1 2 17 ] concluded that with one-step adhesive systems, glycoproteins in saliva adsorb onto the poorly polymerized adhesive layer, thereby preventing adequate co-polymerization.…”
Section: Discussionmentioning
confidence: 99%
“… Adsorption of glycoproteins to the poorly polymerized adhesive surfaces, thus preventing adequate polymerization Rinsing of the contaminant after adhesive application could have disrupted the oxygen inhibited and unpolymerized layer, thereby compromising the co-polymerization with the subsequent resin layer. [ 17 18 19 ] …”
Section: Discussionmentioning
confidence: 99%